Angiotensin Converting Enzyme Inhibitors: Interaction Issues in Patients with Glaucoma and Arterial Hypertension. Review - S. I. Makogon; D. I. Ivanova; A. L. Onishchenko (Oftalʹmologiâ)
The purpose of the review is to evaluate the interaction of angiotensin-converting enzyme inhibitors in patients with glaucoma and concomitant arterial hypertension using literature data. Glaucoma is the main cause of blindness and visual impairment, as well as the main cause of irreversible blindness worldwide. Pharmacotherapy, laser or surgical treatments are used to reduce IOP levels, as well as prevent deterioration of visual field defects. However, 40 % of patients develop glaucomatous neuropathy despite ongoing therapy. This prompts the investigation of alternative causes of damage to the optic nerve, and abnormal blood pressure levels, both too low and too high, are considered as a possible risk factor. Arterial hypertension occurs in 48–65 % of patients with glaucoma and is the most common systemic disease in patients with glaucoma. Currently, angiotensin converting enzyme (ACE) inhibitors are considered the “gold standard” in the treatment of arterial hypertension, in the pathogenesis of which activation of the renin-angiotensin system (RAS) plays an important role. The renin-angiotensin system (RAS) is a hormonal system responsible for regulating blood pressure and fluid and electrolyte balance in the body. Local tissue-specific RAS were found, including in the structures of the eyeball: cornea, aqueous humor, iris, ciliary body, vitreous body, retina. These data indicate that the local RAS plays an important role in the regulation of the physiology of the eye and may become a target in the development of new antiglaucoma drugs. Animal studies, as well as studies in various patient groups, show that systemic antihypertensive drugs that inhibit the RAS, such as ACE inhibitors, reduce IOP. These studies support the concept that RAS inhibitory drugs may be potential antiglaucoma drugs in the future, as ACE inhibitors can improve the outflow of intraocular fluid, thereby reducing IOP.